Assessment of Anaesthetic Impact of Propofol Combined with Isoflurane Versus Sevoflurane for Thoracoscopy in Canines - Gaikwa, Shahir V; Khandekar, Gajendra S; Tripathi, Santosh D; Rani, Monika; Saini, Dishant; Pawshe, Chaitanya H (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was undertaken to evaluate the anaesthetic effect of propofol isoflurane and propofol sevoflurane in twelve dogs with  history of chronic cough, dyspnoea, laboured breathing, nasal discharge, exercise intolerance which were presented to the Department  of Surgery and Radiology, Mumbai Veterinary College and Bai Sakarbai Dinshaw Petit Hospital for Animals, Parel, Mumbai. These dogs  were randomly divided into two equal groups. In both the groups dogs were premedicated with acepromazine (0.04 mg/kg b.wt.)  intravenously, and atropine sulphate (0.04 mg/kg b.wt.) and dexamethasone sodium (0.025 mg/kg b.wt.) SC 10 min before induction  of anaesthesia. In both the groups, anaesthesia was induced with propofol (5 mg/kg b.wt.) intravenously. In group I anaesthesia was  maintained using 2.5% isoflurane and in group II, 2.5% sevoflurane along with oxygen at a flow rate ranging from 500 to 1200 mL/ min. History, physiological parameters, anaesthetic parameters were recorded at different time intervals during the study period. The  present study findings suggest that induction with propofol and maintenance with isoflurane and sevoflurane proved best anaesthetic  technique for thoracoscopy in dogs.
Keywords: Anaesthesia; Dog; , Isoflurane; Thoracoscopy; Sevoflurane.